The Influence of Return On Asset on PBV of Pharmacy Sector Companies in The Indonesian Stock Exchange - Muharram, Andi Iswan; Syachbrani, Warka (Phinisi Applied Accounting Journal, 2024)
This research aims to determine the effect of profitability on company value in the pharmaceutical sector on the Indonesian Stock Exchange.The subjects in this research were Pharmaceutical Sector companies on the Indonesia Stock Exchange from 2019 to 2021. Sampling was carried out using a purposive sampling technique.Data analysis techniques use descriptive statistical analysis, simple linear regression, t test, and coefficient of determination.Based on the research results, ROA has a significant effect on the Price to Book Value of Companies in the Pharmaceutical Sector on the Indonesian Stock Exchange.